Enhanching Employee Green Behavior Through Green Human Resources Management (HRM) and Environmental Knowledge Based on Tri Hita Karana - Widiantari, Komang Sri; Maharani, Made Diah Pradnya; Suidarma, I Made (Universitas Warmadewa, 2024)
One sector of the economy that significantly affects the environment is the hotel business. One of the key strategies used by hotels to mitigate adverse environmental consequences is Green HRM, which aims to lessen the negative effects that arise as part of green initiatives. Furthermore, Tri Hita Karana and environmental knowledge are closely related when it comes to putting sustainable methods into practice and maintaining the environment in a balanced way. The aims of this study is to know whether Green HRM at The Haven Bali Seminyak directly influences Environmental Knowledge and Employee Green Behavior, as well as whether it indirectly influences Employee Green Behavior through Environmental Knowledge based on Tri Hita Karana. In this research, 80 respondents, samples were obtained for data collection methods. This research uses a quantitative approach using the SmartPLS 3.0. From the results of the data analysis carried out, the results obtained are, Green HRM has positively and significantly impacts on Employee Green Behavior, Green HRM has positively and significantly effect on Environmental Knowledge, Environmental Knowledge has positively and significantly impacts on Employee Green. Behavior and Green HRM has positively and significantly impacts on Employee Green Behavior indirectly through Environmental Knowledge.